2019
DOI: 10.1038/d41586-019-01099-5
|View full text |Cite
|
Sign up to set email alerts
|

Rethink government with AI

Abstract: Policymakers should harness data to deliver public services that are responsive, efficient and fair, urge Helen Margetts and Cosmina Dorobantu.Artificial intelligence could one day be used to tailor education to the needs of each individual child. 1 1 A P R I L 2 0 1 9 | V O L 5 6 8 | N A T U R E | 1 6 3 COMMENT SUZANNE KREITER/THE BOSTON GLOBE/GETTY © 2 0 1 9 S p r i n g e r N a t u r e L i m i t e d . A l l r i g h t s r e s e r v e d .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 8 publications
(2 reference statements)
0
41
0
3
Order By: Relevance
“…From the political side, some claim that AI and algorithms will reshape the global order (Wright, 2018) or change interactions among countries (Lee, 2018). From the perspective of public organizations, AI and algorithms may transform processes (Brynjolfsson & McAfee, 2017), be used in the analysis of citizens behavior to understand their needs and deliver public services better suited to those needs (Vogl et al, 2020), verification of eligibility for public services and detection of fraud, or better operational performance of service providers (Margetts & Dorobantu, 2019). At the same time, different authors have recently identified several cases in the public sector implementing AI and algorithm-mediated governance coming from different public service sectors (Desouza, 2018;Sun & Madaglia, 2018) (i.e.…”
Section: Artificial Intelligence and Algorithmic Governancementioning
confidence: 99%
“…From the political side, some claim that AI and algorithms will reshape the global order (Wright, 2018) or change interactions among countries (Lee, 2018). From the perspective of public organizations, AI and algorithms may transform processes (Brynjolfsson & McAfee, 2017), be used in the analysis of citizens behavior to understand their needs and deliver public services better suited to those needs (Vogl et al, 2020), verification of eligibility for public services and detection of fraud, or better operational performance of service providers (Margetts & Dorobantu, 2019). At the same time, different authors have recently identified several cases in the public sector implementing AI and algorithm-mediated governance coming from different public service sectors (Desouza, 2018;Sun & Madaglia, 2018) (i.e.…”
Section: Artificial Intelligence and Algorithmic Governancementioning
confidence: 99%
“…However, a great deal of data is also generated through government's day-to-day interactions and transactions with citizens and businesses. AI has enormous potential for governments to harness these vast quantities of data and provide officials with unprecedented insights, enabling them to improve policy-making processes and to make public services more efficient (Margetts and Dorobantu, 2019). For instance, AI could:  provide more accurate forecasts and predictions, enabling governments to plan more effectively and to target resources and services where they are most needed  tailor public services to user need, allowing governments to adapt the services they offer to individual circumstances  simulate complex systems, from military operations to housing markets, giving governments the opportunity to experiment with policy options and spot unintended consequences before committing to new measures.…”
Section: Issuementioning
confidence: 99%
“…Despite the promise that AI holds for policy making and service delivery, developing and retaining internal expertise on emerging technologies and approaches and their applications within the public sector is a challenge for every government. In the past, governments have struggled to adopt much simpler solutions, such as electronic payroll systems or online appointment booking systems (Margetts and Dorobantu, 2019).…”
Section: Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Los portales de gobierno facilitan la diseminación y utilización de los datos que los gobiernos recolectan, los cuales pueden ser re-utilizadas para diversas políticas públicas y sociales, bajo la premisa de producir valor público, al promover la innovación, la co-creación, y participación en el quehacer gubernamental (Rodríguez-Navas y Morales, 2018; Mulgan, 2016). No obstante, la utilización de la información publicada en los portales de transparencia para el diseño, implementación y gestión de políticas públicas no ha sido tan efectiva (Margetts & Dorobantu, 2019).…”
Section: N T R O D U C C I ó Nunclassified